Inhibition of the renin–angiotensin system improves physiological outcomes in mice with mild or severe cancer cachexia. Issue 5 (16th March 2013) - Murphy, Kate T.; Chee, Annabel; Trieu, Jennifer; Naim, Timur; Lynch, Gordon S.
<x xml:space="preserve">Abstract</x> Cancer cachexia describes the progressive skeletal muscle wasting and weakness associated with many cancers. Cachexia reduces mobility and quality of life and accounts for 20–30% of all cancer‐related deaths. Activation of the renin–angiotensin system causes skeletal muscle wasting and weakness. We tested the hypothesis that treatment with the angiotensin converting enzyme (ACE) inhibitor, perindopril, would enhance whole body and skeletal muscle function in cachectic mice bearing Colon‐26 (C‐26) tumors. CD2F1 mice received a subcutaneous injection of phosphate buffered saline or C‐26 tumor cells inducing either a mild or severe cachexia. The following day, one cohort of C‐26 mice began receiving perindopril in their drinking water (4 mg kg−1 day−1) for 21 days. In mild and severe cachexia, perindopril increased measures of whole body function (grip strength and rotarod) and reduced fatigue in isolated contracting diaphragm muscle strips (p < 0.05). In severely cachectic mice, perindopril reduced tumor growth, improved locomotor activity and reduced fatigue of tibialis anterior muscles in situ (p < 0.05), which was associated with increased oxidative enzyme capacity (succinate deyhydrogenase, p < 0.05). Perindopril attenuated the increase in MuRF‐1 and IL‐6 mRNA expression and enhanced Akt phosphorylation in severely cachectic mice but neither body nor muscle mass was increased. These findings support the therapeutic potential of ACE inhibition for enhancing whole body function and reducing fatigue of respiratory muscles in early and late stage cancer cachexia and should be confirmed in future clinical trials. Since ACE inhibition alone did not enhance body or muscle mass, co‐treatment with an anabolic agent may be required to address these aspects of cancer cachexia.